ANALYSIS OF C:N:P RATIO IN THE SEDIMENT OF SEAGRASS ECOSYSTEM IN THE COASTAL WATERS OF JAGO-JAGO NORTH SUMATRA PROVINCE - Juni Artha Hasibuan; Zulkifli '; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in January-Februari 2015 in coastal waters of Jago-Jago, North Sumatera.The aims ofthis study were to determine the nutrient content of sediment in seagrass ecosystem and to determine the ratio of C:N:P in the sediments by different sediment characteristics and determine the relationship of nutrient with density and biomass of seagrass. The parameters measured were included physical and chemical parameters of marine waters. The density was computed using a quadratic transect, while seagrass biomass was calculated by measuring dry weight of shoot. The value ratio of C:N:P in the sediment was obtained through the determination of carbon (C) in total by the method of Walkley & Black, total of nitrogen by Kjehdahl method and phosphorus total with Double Acid method. The results showed the average carbon content was 1.32117 to 2.47813%, the average nitrogen content was 0.63114 to 1.5468% and the average phosphorus was from 0.00002 to 0.0004%. The density of seagrass in the village of Jago-Jago was between 29 to 56.3 shoots/m2 and biomass of seagrass was between 651.26 to 1261.34 g/m2. Station III had a ratio of C:N:P =12011:14062:1 and provided good leverage, this can be indicated also by the total biomass and density of seagrass at this station was the highest. The C-organic, Nitrogen and Phosphorus in the sediment with density and biomass of seagrass had a weak relationship, there are other factors that might affect the density and biomass of seagrass in which were not measured in this study.keyword : Density, Biomass, Seagrass Ecosystems, Ratio of C:N:P, Sediment, Jago-Jago Coast